Comparative assessment of improved management practices for paddy yield in Eastern Indo-Gangetic Plains - SINGH, A K; MALIK, R K; KUMAR, ANJANI; SINGH, ATAR; BURMAN, R ROY; ROY, PINAKI (The Indian Journal of Agricultural Sciences, 2019)
Rice is grown around the globe in 113 countries spread over 153 million hectares with estimated total production of 589 million tonnes. Eastern Indo-Gangetic Plains (EIGP) of India contributes major portion in food grain production most particularly in rice but with a low productivity as compared to Western Indo-Gangetic Plains (WIGP) of India. Therefore, field experiment on technological interventions that are fundamental to productivity growth of rice were successfully implemented through farmers’ field trials by 10 Krishi Vigyan Kendras (KVKs) across different ecologies in Bihar (8 KVKs), Eastern UP (2 KVKs) during 2016–18. It was found that paddy yield remained same in a range of 5.1 to 5.2 for Long Duration Rice Varieties (LDRVs) and in a range of 5.0 to 5.1 tonnes/ha for Medium Duration Rice Varieties (MDRVs) or hybrids. The grain yield of wheat saw a significant advantage with rice equivalent wheat yields (3.2 tonnes/ha) under CTW and 3.8 tonnes/ha under ZTW. Work done by KVKs (Ara, Buxar and Rohtas) show that creation of rice nursery enterprise (RNEs) can be an alternate way to transplant rice on time. The RNEs created by three KVKs in Bihar, raised nursery on 27.86 acres which was transplanted on 983 acres. When DSR was practiced after pre-sowing irrigation and good field preparation, the paddy yields ranged from 6.2 to 6.4 tonnes/ha in the cluster of 5 KVKs from Agro-Climatic Zone III (Southern East and West), 5.4 to 5.8 tonnes/ha in the cluster of 3 KVKs fromAgro-Climatic Zones I(Northern West) and 5.1 to 5.2 in the eastern UP cluster of 2 KVKs.